RETRACTED ARTICLE: Mirt2 functions in synergy with miR-377 to participate in inflammatory pathophysiology of Sjögren's syndrome - Miaomiao Xin; Hongda Liang; Hongyue Wang; Dawei Wen; Liqin Wang; Lei Zhao; Mingshu Sun; Jibo Wang (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
We, the authors, Editors and Publisher of the journal Artificial Cells, Nanomedicine and Biotechnology have retracted the following article:Miaomiao Xin, Hongda Liang, Hongyue Wang, Dawei Wen, Liqin Wang, Lei Zhao, Mingshu Sun & Jibo Wang (2019) Mirt2 functions in synergy with miR-377 to participate in inflammatory pathophysiology of Sjögren’s syndrome. Artificial Cells, Nanomedicine, and Biotechnology, 47(1), 2473–2480, DOI: 10.1080/21691401.2019.1626413Following publication of the article, concerns were raised in 2019 regarding the western blots presented in the article; an Expression of Concern was issued as the authors were unable to provide the original data for review. In 2023, the authors alerted the Publisher that their Western Blots, in particular figures 1 (c,d), 3 (g,h,i,j), 5 (a,b) and 6 (a,b) had been edited prior to publication to unify the background of the blots. They also notified the publisher that they were unable to repeat their experiments to replicate their results.Upon further review, the Editor and Publisher found additional concerns regarding animal ethics and methodology. As this directly impacts the validity of the reported results and conclusions the authors alerted the issue to the Editor and Publisher, and all have agreed to retract the article to ensure the integrity of the scholarly record.We have been informed in our decision-making by our editorial policies and integrity and the COPE guidelines.The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.